Comparación del proceso de cicatrización entre el Alveolex y Hemocolágeno en cirugía de terceras molares, facultad de odontología, Universidad Nacional de la Amazonía Peruana, 2023 - Puente Alvaro, Mayte Gianella (2023)
The objective of this report was to compare the healing process between Alveolex and Hemocollagen in third molar surgery, Faculty of Dentistry, National University of the Peruvian Amazon, 2023; working under a quantitative approach of experimental design, made up of a population of 60 students who underwent third molar surgery, to whom the observation sheet was used to collect information. After the results analyzed, it was concluded that the complete healing when using Alveolex is evident in all case, analyzed after 14 days, likewise, the Hemocollagen presents absence of healing in 55% and the difference has only achieved partial healing. Regarding the signs of inflammation at 14 days, there is evidence of its absence when using any of the two materials. Regarding the postoperative pain at 14 days, the absence of pain is evident almost in its entirety when using any of the two materials. In short, both materials are equally effective for patients undergoing this type of surgery, since no difference in the expected results has been identified.